Faktor - Faktor Penyebab Terjadinya Karies Gigi pada Siswa Sekolah Dasar - Sainuddin; Angki , Johnny; S, Rahmawati; Bahtiar (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Dental caries and periodontal disease are the most common dental and oral diseases suffered by people in Indonesia. When a child's first tooth erupts, the process of developing caries in children can begin. Oral hygiene is closely related to caries, especially in children. According to WHO, 90% of school children globally, including in Indonesia, are said to have experienced dental caries. The aim of this study was to determine the relationship between causal factors and the occurrence of dental caries. The method used in this study was a survey with a cross-sectional approach. This research was conducted at SDN 90 To Cemba, Alla district, Enrekang Regency with a sample of 45 students from class V-VI and it was carried out on January 17-19 2023. Results This study obtained the results of the chi-square test statistically, the influence between knowledge about dental caries and dental caries rates obtained a value of p <0.050, namely 0.007, the effect between the habit of brushing teeth and the number of dental caries obtained a value of p <0.050, which is equal to 0.035, while the conclusion is The influence between the habit of eating cariogenic food and the incidence of dental caries obtained a value of p<0.050 which is equal to 0.002. There is a relationship between knowledge about dental caries and the occurrence of dental caries. There is a relationship between the habit of brushing teeth and the occurrence of dental caries. There is a relationship between the habit of eating cariogenic food and occurrence of dental caries Keywords: Factors causing dental caries; dental caries status; elementary school age children